Urban Transit Infrastructure and Inequality - Lee, Kwok Hao; Tan, Brandon Joel (The Review of Economics and Statistics, 2026)
We propose a quantitative spatial model featuring heterogeneous worker groups and their travel to consume nontradable goods and services. We consider the opening of the Downtown Line in Singapore, which connected regions where high-income households have residential amenities to where nontraded sectors are productive. Leveraging transit farecard data, we show that high-income workers saw large welfare gains but low-income workers gained little. Everyone enjoyed improved access to consumption opportunities, but low-income jobs in nontradables moved to less attractive workplaces. Abstracting from consumption travel understates the disparate impact across worker groups threefold.